Antarctic krill antioxidant peptides show inferior IgE-binding ability and RBL-2H3 cell degranulation - Jie Ding; Chunyan Zhu; Pengfei Jiang; Libo Qi; Na Sun; Songyi Lin (Food Science and Human Wellness)
Enzymatic hydrolysis, isolation, and purification might make a great deal of difference in antioxidant activity and antigenicity of peptide components. This study aimed to isolate and purify antioxidant peptide components from Antarctic krill and evaluate their allergenicity of them. Electron paramagnetic resonance (EPR) spectroscopy results indicated 310 kDa Antarctic krill hydrolysates (AKHs) had higher DPPH and ·OH radical scavenging rates. And the second component (N2-2) purified 310 kDa hydrolysate showed better ability to scavenge DPPH and ·OH radicals (P < 0.05), which were (47.43 ± 2.18)% and (34.33 ± 1.25)%, respectively. Additionally, indirect-ELISA results revealed that N2-1 had a weaker ability to bind specific IgE and that N2-2 had a lower binding capability to specific IgG1 (P < 0.05). And N2-2 had a higher EC50 value of (5.29 ± 0.95) ng/mL (P < 0.05) in cell degranulation assay, which was about 13.80 times that of Antarctic krill. Therefore, N2-2 might be the potential source of the antioxidant peptides with lower allergenicity.